Hubungan Ekspresi Transforming Growth Factor-β1, Fibroblast Activated Protein, pola Tumor-Associated Collagen Signature dan derajat Tumor-Infiltrating Lymphocytes terhadap Grading International Society of Urological Pathology pada Clear Cell Renal Cell Ca - Kharismawaty, Dina; Delyuzar, Delyuzar; Betty, Betty; S Lukito, Joko; Chrestella, Jessy (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2023)
BackgroundClear cell renal cell carcinoma (ccRCC) is a very aggressive cancer and is often diagnosed at an advanced stage. The stromal component around the tumor is thought to have contributed greatly to these findings.MethodsAnalytical study with cross sectional design on 23 histological specimens diagnosed by ccRCC based on data from medical records/pathology archives in 2012-2021. Each specimen was stained with hematoxylin and eosin, TGF-β and FAP immunohistochemistry and Masson's trichrome. Fisher's exact test (p<0.05) was used to assess the association between the expressions of all variables with the ISUP grading.ResultsMost cases were high grade ccRCC (87%) samples, of which 73.9% samples expressed strong TGF-β, 82.7% samples expressed positive intratumoral FAP, 78.3% samples expressed positive stromal FAP, 47.8% showed a TACS-3-pattern, 56.5% of samples with positive stromal TILs and 47.8% of samples with negative intratumoral TILs. There was no significant association between all of these variables and the ISUP grading of the ccRCC (p<0.05).ConclusionExpression of TGF-β1, intratumoral and stromal FAP, TACS pattern and the degree of intratumoral and stromal TILs were not significantly associated with ISUP grading in ccRCC.